Blurring public and private security in Indonesia: corporate interests and human rights in a fragile environment - White, Nigel D.; Footer, Mary E.; Senior, Kerry; Dorp, Mark van; Kiezebrink, Vincent; Wasi Gede Puraka, Y.; Anzas, Ayudya (Springer, 2018)
While legal and policy frameworks are based on a clear distinction between public and private security actors and functions, the reality on the ground in Indonesia reveals that there is a high level of corporate capture of public security services, including the military and police, who often operate alongside private security companies (mainly local, though there is some evidence of an emerging international presence), and the security personnel of companies engaged in the natural resources industry. This has led to serious human rights violations of indigenous peoples and other local inhabitants, who often find themselves entangled in protracted conflicts with multinational companies over access to their land. Two case studies involving fieldwork in the logging and palm oil sectors in Sumatra reveal a pernicious and deliberate erosion and violation of rights of local inhabitants across the spectrum of security actors, showing that public security actors are protecting corporate interests rather than performing public functions. The implications of these findings are considered in terms of legal responsibilities as well as access to justice. The article reasons towards what are argued to be necessary legal and policy changes.